2012
DOI: 10.3109/15368378.2012.661699
|View full text |Cite|
|
Sign up to set email alerts
|

Pulsed electromagnetic field: an organic compatible method to promote plant growth and yield in two corn types

Abstract: Pre-sowing treatment of pulsed electromagnetic fields was used in corn seeds, in both indoor and outdoor conditions, in order to investigate the effect on plant growth and yield. The results of this research showed that pulsed electromagnetic fields can enhance plant characteristics, both under controlled environmental conditions and uncontrolled field conditions. The two varieties responded differently in the duration of magnetic field. Seeds were treated for 0, 15, 30, and 45 min with pulsed electromagnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 19 publications
1
16
0
3
Order By: Relevance
“…Pulsed electromagnetic fields showed could replace hormones in vegetative propagation of oregano, stimulating rooting process in stem cuttings [13]. Enhancements of plant characteristics with economic impact on producer's income could be the future of modern, organic, and sustainable agriculture [14]. Furthermore, the adoption of organic cultural system could reduce energy inputs [15].…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed electromagnetic fields showed could replace hormones in vegetative propagation of oregano, stimulating rooting process in stem cuttings [13]. Enhancements of plant characteristics with economic impact on producer's income could be the future of modern, organic, and sustainable agriculture [14]. Furthermore, the adoption of organic cultural system could reduce energy inputs [15].…”
Section: Introductionmentioning
confidence: 99%
“…Seeds that have been exposed to MF for 30 and 45 min have been found to perform the best results with economic impact on producer's income in a context of a modern, organic, and sustainable agriculture (Bilalis et al, 2012). …”
Section: Exposure Of Plants To Mf Intensities Higher Than the Geomagnmentioning
confidence: 99%
“…Numerous experimental evidence has suggested that such treatments can improve seed germination, increase the size and the robustness of plants, and enhance production yields (reviewed in References [1][2][3][4][5][6][7]). So far, the investigations have mostly focused on the effects of treatments on seed germination and early seedling growth; although some alterations of physiological and biochemical parameters have also been reported, such as changes in seed enzyme activities, [8][9][10] sugar content, [8,11] photosynthetic indices, [12,13] the amount of photosynthetic pigments, [14][15][16] and secondary metabolites [12,17] in seedling leaves. Long-term observations have revealed that the effects of presowing seed treatment with CP and EMF on plant growth may persist for the entire vegetation season [18][19][20][21] or even several seasons in perennials, [22,23] and the changes induced on a longer time scale can be much larger in comparison to those induced in germination.…”
Section: Introductionmentioning
confidence: 99%